(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Nutritional status is closely related to high cholesterol levels. High cholesterol levels as a trigger for other metabolic diseases. Fruits high in fiber and vitamin C can be used to keep blood cholesterol levels regularly. Aim: To determine the effect of red dragon fruit on blood cholesterol levels in people with excessive nutritional status. Methods: Research used an experimental approach with a pretest and post-test control group design. The sample consisted of 2 groups, namely the control group and the intervention group, with 50 respondents in each group. The sample was taken using purposive sampling. The intervention group got red dragon fruit juice for seven days. Blood cholesterol levels are measured by laboratory tested using intravenous blood. The statistical test used the Paired T-Test and Independent T-Test. Results: The difference mean posttest-pretest control group and intervention groups were 13.56 mmHg and -13.06 mmHg. The analysis of pretest-posttest blood cholesterol levels among the control and intervention groups were p=0.514 and p=0.035. The difference between the control group and the intervention group was 0.022. Conclusion: Red dragon fruit is effective in reducing blood cholesterol levels in people with excessive nutritional status.